The mine wars [videorecording (DVD)] - Murphy, Michael, 1938-; Green, James R., 1944-2016; Green, James R., 1944-2016 (PBS Distribution, 2016)
At the beginning of the 20th century, coal was the engine of American industrial progress. Nearly three quarters of a million men across the country spent ten or twelve hours a day underground in coal mines. The Mine Wars brings to life the struggle that turned the coalfields of southern West Virginia into a blood-soaked war zone where basic constitutional rights and freedoms were violently contested.